Optimizing WEDM Parameters on Nano-SiC-Gr Reinforced Aluminum Composites Using RSM - R. Saravanan; G. Anbuchezhiyan; Vamsi Krishna Mamidi; Palani Kumaran (Advances in Materials Science and Engineering)
Nanocomposites are preferred for performance enhancement over micron composites because of their better performance in enhancing the desired properties of the parent material. Nano-silicon carbide and nano-graphite are considered together for reinforcement of Al7075 in this piece of research. Here, the purpose of reinforcement of graphite considered is to improve machinability. The stir casting was employed for fabrication of nanocomposite. The composite matrix includes Al7075 matrix material, reinforcement material of nano-SiC (5 wt.%), and nano-graphite (5 wt.%). Wire cut Electrical Discharge Machining (WEDM) of the synthesized nanocomposite SiC/Gr/Al7075 is considered for investigating the machinability. The objectives of the study are to synthesize the novel nanocomposite and optimize the process parameters to minimize the kerf width during WEDM. The independent variables like choice of wire electrode including the uncoated brass wire, diffused annealed wire, and zinc coated brass wire were considered along with operating parameters like gap voltage, pulse-off time (Toff), and pulse-on time (Ton). The response surface methodology (RSM) is used for designing experiments and analyzing and optimizing independent parameters of WEDM for minimizing the kerf width. Experimental results reveal that the machinability performance of the novel nanocomposite in WEDM with zinc coated brass wire was the best and produced minimum kerf width with the optimized inputs of 117 μs pulse-on time, 60 μs pulse-off time, 160A input current, and 10 volt gap voltage.